Erratum to: “Anxiety and neurometabolite levels in the hippocampus and amygdala after prolonged exposure to predator-scent stress” - O. B. Shevelev; V. E. Tseilikman; N. V. Khotskin; A. S. Khotskina; G. V. Kontsevaya; M. S. Lapshin; M. P. Moshkin; M. V. Komelkova; I. V. Feklicheva; O. B. Tseilikman; E. B. Manukhina; H. F. Downey; et al. (Вавиловский журнал генетики и селекции)
.